DEVELOPMENT OF OPERATIONAL MODEL FOR CONTAINER TERMINAL USING AGENT BASED SIMULATION - NURJAMAN (NIM: 23414007), SIDIK
Ports in particular container terminals are a national logistics infrastructure. Word Bank (2016) explained that Indonesia's logistics performance index ranked 63th with a score of 2.98. This indicates that the performance of national logistics is still worse then other countries. Therefore, it is necessary to improve the national infrastructure, especially container terminal as a contributing sector of 51.5% of national gross domestic revenue (GDP). This research develops a model for improving the existing system using a multiagent system approach and discrete events. The problem of the container terminal operating system is a complex problem, so the solution will be searched by simulation. The solution searched by multi-agent system model design and simulation using Anylogic. The results of the model test show that the infrastructure at the JICT container terminal should be added. Infrastructure is the equipment used to serve the process of loading and unloading, namely quay cranes. The number of quay cranes required to serve large docks are 4 units and a small dock are 2 units. The addition of equipment made resulted in decreased turnaround time by 4 hours compared to turnaround time when applying actual policy. So it can be concluded that the proposed policy give better results than the actual policy.